THE “ACCULTURATIVE ISLAM” AS A TYPE OF HOME-GROWN ISLAMIC TRADITION: Religion and Local Culture in Bali (State Islamic University (UIN) of Sunan Ampel Surabaya, 2019)
Religion and culture are inextricably connected like two sides of the same coin because in understanding the religion properly often requires knowing the culture that shaped it, and vice versa. This paper reports on the research of how Islam has interacted with Balinese Hinduism for several hundred years. Using historical-anthropological study with a phenomenological approach, this study has revealed that religious traditions practiced by Balinese Muslims are identical to the Hinduism-based local culture. It means that the existence of local culture in Bali highly influences Islamic practices, which are certainly distinct from those in the Middle East, especially Saudi of Arabia, as the cradle of Islam. The expressions of Islam are resulted from the dialogue between Islamic traditions with local culture, Hindu tradition in particular, which shapes Balinese’s distinctive Islamic identity that is more progressive, tolerant, and egalitarian.